2004
DOI: 10.1139/v04-143
|View full text |Cite
|
Sign up to set email alerts
|

The complex photochemistry of 2,3-dibenzylidenesuccinates

Abstract: The photochemistry of diethyl E,E-2,3-(3,4,5-trimethoxybenzylidene)succinate (8) is solvent dependent. In both protic and aprotic solvents, there is a photoequilibrium established between 8 and its E,Z-isomer (9). In chloroform at high light intensity, very little 9 is formed and the main product is 1,4-dihydronaphthalene (10), formed via photoinduced intramolecular [1,3]-sigmatropic hydrogen shift within an intermediate 1,8a-dihydronaphthalene (11). In protic solvents, irradiation of either 8 or 9 ultimately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…13 (7). To an oven dried 250 mL three-necked round-bottom flask, equipped with a stirring bar and flushed with argon, 2.22 g (1.1 eq., 19.77 mmol) of t-BuOK was inserted, and was suspended in 65 mL of dry toluene. To the vigorously stirred suspension, a solution of 3.53 g (1 eq., 17.97 mmol) of 3,4,5-trimethoxybenzaldehyde and 5.0 g (1 eq., 17.97 mmol) of ester 6 in 50 mL of dry toluene was added dropwise.…”
Section: General Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 (7). To an oven dried 250 mL three-necked round-bottom flask, equipped with a stirring bar and flushed with argon, 2.22 g (1.1 eq., 19.77 mmol) of t-BuOK was inserted, and was suspended in 65 mL of dry toluene. To the vigorously stirred suspension, a solution of 3.53 g (1 eq., 17.97 mmol) of 3,4,5-trimethoxybenzaldehyde and 5.0 g (1 eq., 17.97 mmol) of ester 6 in 50 mL of dry toluene was added dropwise.…”
Section: General Experimental Methodsmentioning
confidence: 99%
“…Solvent protonation at C-2 was previously described as an alternative mechanism to a concerted [1,5]-sigmatropic hydrogen shift. 19 Indeed, we succeeded to obtain the desired product 12 when irradiation was performed in methanol. Further experiments confirmed that the use of an acidic additive (0.01 mM TFA) further accelerated the reaction, and helped to avoid excessive photolytic degradation, as proposed previously by Charlton.…”
Section: Photocyclization Of 10mentioning
confidence: 99%
See 1 more Smart Citation